PEMANFAATAN LIMBAH KOTORAN AYAM SEBAGAI BAHAN BAKU PEMBUATAN KOMPOS - Efratenta Katherina Defari; Deselina ,; Gunggung Senoaji; Fajrin Hidayat (DHARMA RAFLESIA, 2017)
Farm poultry, especially chicken, is a producer of meat and eggs. In addition to producing meat and eggs, chicken farms also have negative impacts, which can cause odorless gasthat can pollute the environment. In the village there are six places Srikaton laying chickenfarms that always make chicken manure every day. Alternative technology that can beapplied and has a positive outlook is to convert poultry farm waste, ie chicken manure intocompost. IBM outer target groups laying chicken farming is to produce compost chickenthat can be utilized by the villagers Srikaton (short-term targets), and the long-term targetis to sell the compost to other consumer good in the village Srikaton, and outside thevillage Srikaton . Effective technology for the transformation of society is using extensionmethods, training by making demonstrations, or direct practice coupled with mentoring.The target of this service is Srikaton village community, which consists of chickenbreeders, youth organization group, the PKK, and residents who do not have a job(unemployed). Based on the activities carried out, the people were very enthusiastic.Through these activities, the village Srikaton has the skills to produce compost chickenmanure that can be used for fertilizer in the garden itself, and or for sale, so as to improvetheir welfare.Keywords: chicken manure, compost